2020
DOI: 10.15517/am.v31i2.38615
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de la productividad agrícola-económica sustentable y convencional de papaya, en Michoacán, México

Abstract: Introducción. En Buenavista, Michoacán, México, la superficie sembrada de papaya (Carica papaya L.) es de la variedad Maradol Roja y la mayoría de los agricultores utilizan un modelo de producción agrícola convencional, donde no se conoce con certeza la productividad ni la rentabilidad del cultivo; conocer estas dos variables permitiría obtener una producción eficiente que a mediano plazo mejoraría el entorno socioeconómico de los agricultores. Objetivo. Comparar un modelo de producción agrícola sustentable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Two papaya farming models were recently assessed. The authors observed that the sustainable model achieved a CBR of 2.24 and an equilibrium point of 38.47%, while the conventional model allowed a CBR of 1.08 and an equilibrium point of 90.11% [4]. The authors conclude that the conventional model is economically unfavorable, while the sustainable model is economically attractive and presents a better use of local natural resources.…”
Section: Economic Profitabilitymentioning
confidence: 95%
See 2 more Smart Citations
“…Two papaya farming models were recently assessed. The authors observed that the sustainable model achieved a CBR of 2.24 and an equilibrium point of 38.47%, while the conventional model allowed a CBR of 1.08 and an equilibrium point of 90.11% [4]. The authors conclude that the conventional model is economically unfavorable, while the sustainable model is economically attractive and presents a better use of local natural resources.…”
Section: Economic Profitabilitymentioning
confidence: 95%
“…The authors conclude that the conventional model is economically unfavorable, while the sustainable model is economically attractive and presents a better use of local natural resources. The observed differences in the studies might be due to market conditions (price), offer and demand at the time of the transaction, as well as to environmental and technical factors during the agronomic management of the crop [4].…”
Section: Economic Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Durante la primera floración se eliminaron las plantas con floración masculina (desmache), para dejar 600 plantas hermafroditas establecidas en 2400 m 2 de terreno, considerado como la parcela experimental. Se fertilizó al suelo con la dosis de 140 N -120 P -100 K, fraccionada en cuatro partes, correspondientes a las etapas fenológicas más demandantes del cultivo (Miranda-Ramírez et al, 2018): la primera en el trasplante al fondo de la cepa en el mes de marzo; la segunda en la zona de goteo al momento del desmache 65 días después; la tercera en la floración 32 días después; y la cuarta al inicio del crecimiento del fruto cuatro meses después. Las fuentes fertilizantes fueron sulfato de amonio, fosfato di-amónico, triple 17, urea y superfosfato de calcio triple.…”
Section: Materiales Y Métodosunclassified
“…In Mexico, the cultivation of the Maradol variety predominates, with a yield of 1,196,300.74 t in 2022. The production of this fruit is led by the states of Oaxaca, Colima, Chiapas, Veracruz and Michoacán, which together produce more than 80% of this fruit at the national level (Granados et al, 2015;Miranda-Ramírez et al, 2020;SIAP, 2023;Cisneros-Sanguilán et al, 2023).…”
Section: Introductionmentioning
confidence: 99%